Automated class student counting through image processing - Agyan Panda; Azadeh Shemshad (Big Data and Computing Visions)
Teachers used to keep student records manually by calling names or distributing an attendance sheet around the classroom. These procedures take time, are prone to errors, and require proxy attendance. Furthermore, digital record assimilation is time-consuming since teachers must manually put in the entries in the database to generate reports. It's also important to keep manual and digital records consistent. Standard biometrics such as fingerprint and iris recognition have been used in automated systems in recent years. These systems are obtrusive by nature and necessitate high-tech equipment. Our proposed solution eliminates redundancy in human records and makes maintaining attendance a simple chore.